Journalistic Translation: Procedures and Strategies in English-Kurdish Translation of Media Texts (Cambridge Scholars Publishing, 2019)
This volume painstakingly formulates a composite model of translation procedures that covers both linguistic and cultural aspects inherent in translation. The model is based on an integration of three classic taxonomies of translation procedures proposed by influential translation scholars, namely Vinay and Darbelnet (1995), Newmark (1988), and Dickins, Hervey and Higgins (2002/2016). The book combines these three taxonomies into an integrated model and extends it, effectively, to identify patterns of translation procedures and overall strategies in English-Kurdish translation of journalistic texts. The book is a breakthrough in the field of journalistic translation between the two languages. -- -- With a clear definition and exemplification of each translation procedure, the importance of the model is that it is replicable for future descriptive translation studies and can be carried out in other language pairs and on other genres. Moreover, the model is comprehensive in nature, and covers almost all translational changes and shifts that may occur in the translation process. Thus, this model of translation procedures transcends previous frameworks in such a way that prospective translation researchers will not need to go back to these older models of translation procedures.
https://katalog.adlr.link/Record/51-9781527528079